Ulmus davidiana var. japonica Extracts Suppress Lipopolysaccharide-Induced Apoptosis Through Intracellular Calcium Modulation in U937 Macrophages - Yun, Jang-Hyuk; Kim, Hyun-Ouk; Jeong, Jae-Hun; Min, Yerin; Park, Kwang-Hyun; Si, Chuanling; Choi, Sun-Eun (Frontiers in Energy Research, 2022)
This study was aimed to examine the antiapoptotic effect of Ulmus davidiana extracts through regulation of the intracellular cation mobilization in U937 human monocytic cells. To investigate the modulatory effects on lipopolysaccharide-induced apoptosis and the Ca2+ signaling pathway, we measured the levels of intracellular Ca2+ and various protein markers such as Bax, Bcl-2, and PARP. To isolate biopotent molecules, the branches of U. davidiana were processed sequentially using 60% ethanol, supercritical fluid extraction, and ethyl acetate extraction of the remaining samples to obtain single fractions and catechin-glycoside, which is one of the known bioeffector molecules of U. davidiana. Lipopolysaccharide increased intracellular Ca2+ mobilization in U937 cells by inducing transient oscillations and markedly increased Bax and PARP protein expression and decreased Bcl-2 expression. All U. davidiana and catechin-glycoside significantly reduced lipopolysaccharide-induced intracellular Ca2+ mobilization and downregulated apoptosis-related molecules. These results suggest that U. davidiana and catechin-glycoside may be useful for improving immune system function.